Statistical Principles and Techniques in Scientific and Social Research. - Krzanowski, Wojtek J. (Oxford University Press, UK, 2007)
This text provides a clear discussion of the basic statistical concepts and methods frequently encountered in statistical research. Assuming only a basic level of Mathematics, and with numerous examples and illustrations, this text is a valuable resource for students and researchers in the Sciences and Social Sciences. - ;This graduate-level text provides a survey of the logic and reasoning underpinning statistical analysis, as well as giving a broad-brush overview of the various statistical techniques that play a major role in scientific and social investigations. Arranged in rough historical.